Enhanced Carbon Neutral and Performance Characteristics Cookstove for Energy Sustainability - Samson Kolawole Fasogbon; Emmanuel Segun Durowoju; Theophilus Chibuzo Uzoh; Kubiat Edeheudim George; Mark Onons Ikhifa; Timilehin Daniel Adegoke; Ibrahim Ademola Fetuga (The Journal of Engineering and Exact Sciences)
Open fire cooking, which consists of either three stones arrangement in a triangular shape or iron three legs fabricated stove (Adogan), is a common way of cooking in developing and underdeveloped countries. Surely this method of cooking is simple, but comes with its inherent problems that threaten energy sustainability concept; in a way of its harmful gases emissions, high cost; as occasioned by thermal inefficiency which also culminates in to high depletion rate; and ultimately deforestation. These energy sustainability factors and time wastages on wood fetching; had led significant number of researchers to investigate improvement process of the traditional cookstove; and have therefore developed some enhanced cookstoves for use. The article is aimed at designing an enhanced carbon neutral and performance characteristics cookstove for energy sustainability. Analytical basis, experimental studies and performance testing were conducted on existing improved traditional stove; with three burners of orifice sizes 0.8cm, 1.0cm, and 1.2cm. The model with burner orifice size 1.2cm presented highest thermal efficiency, lowest specific fuel consumption and lowest CO ppm. The study arrived that for any enhanced traditional cookstove to give optimal energy sustainability model, burner orifice size of 1.2 cm should be employed.